Kamus super lengkap Arab Inggris Indonesia / Moh. Tohiri Habib, Nurul Huda, Rusdianto; editor, Sidna Jabir - Moh. Tohiri Habib, ; Nurul Huda ; Rusdianto ; Sidna Jabir (DIVA Press, 2017)
844 halaman : ilustrasi ; 24 cm.